Phytoconstituents in the Management of Covid-19: Demystifying the Fact - Barkat, Md. Abul; Kaushik, Pawan; Barkat, Harshita Abul; Khan, Mohammad Idreesh; Hadi, Hazrina Ab (Drug Research, 2022)
The 2019-nCoV (COVID-19; novel coronavirus disease-2019) outbreak is caused by the coronavirus, and its continued spread is responsible for increasing deaths, social and economic burden. COVID-19 created a chaotic situation worldwide and claimed the lives of over 5,027,183 and 248,467,363 confirmed cases have been reported so far as per the data published by WHO (World Health Organization) till 5th November 2021. Scientific communities all over the world are toiling to find a suitable therapeutic drug for this deadly disease. Although till date no promising drug has been discovered for this COVID-19. However, as per the WHO, over 102 COVID-19 vaccines are in clinical development and 185 in pre-clinical development. Naturally occurring phytoconstituents possess considerable chemical richness in the form of anti-viral and anti-parasitic potential and have been extensively exploited for the same globally. Still, phytomedicine-based therapies are considered as the best available treatment option to minimize and treat the symptoms of COVID-19 because of the least possible side effects compared to synthetic drugs recommended by the physicians/clinicians. In this review, the use of plant chemicals as a possible therapeutic agent for severe acute respiratory syndrome coronavirus 2 (SARS CoV2) is highlighted with their proposed mechanism of action, which will prove fruitful and effective in finding a cure for this deadly disease.
Keywords: Coronavirus; COVID-19; Phytochemicals; SARS-CoV2; Phytomedicine; clinical and pre-clinical development